2015
DOI: 10.1099/mgen.0.000027
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific diversification of the highly virulent serotype 1 Streptococcus pneumoniae

Abstract: Serotype 1 Streptococcus pneumoniae is a leading cause of invasive pneumococcal disease (IPD) worldwide, with the highest burden in developing countries. We report the whole-genome sequencing analysis of 448 serotype 1 isolates from 27 countries worldwide (including 11 in Africa). The global serotype 1 population shows a strong phylogeographic structure at the continental level, and within Africa there is further region-specific structure. Our results demonstrate that regionspecific diversification within Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 46 publications
8
48
0
Order By: Relevance
“…We observed the distribution of genetic recombination events consistent with previous studies [15,50,58]. The mean sizes of the recombination events varied significantly (p < 0.0001) between the SCs and the mean sizes ranged from 4650 bp to 75156 bp ( Table 1).…”
Section: Genetic Recombination In the St217 Sequence Clusterssupporting
confidence: 89%
See 3 more Smart Citations
“…We observed the distribution of genetic recombination events consistent with previous studies [15,50,58]. The mean sizes of the recombination events varied significantly (p < 0.0001) between the SCs and the mean sizes ranged from 4650 bp to 75156 bp ( Table 1).…”
Section: Genetic Recombination In the St217 Sequence Clusterssupporting
confidence: 89%
“…The rarity of serotype 1 isolates in carriage has led to the hypothesis it has a lower rate of recombination due to limited opportunities for genetic exchange during carriage [14]. A recent report has identified the presence of genetic recombination in a global serotype 1 population [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we also obtained 3.3% and 70.5% of intermediate and full resistance to tetracycline, indicating circulation in carriage of tetracycline resistant isolates among children aged 0 to 2 year old. High level of resistance to tetracycline (84%) was already observed in clinical isolates of serotype1 SPN from Niger in which, tet (M) gene coding for resistance to tetracycline was found [26]. Though progressively being abandoned for its toxicity (National treatment guidelines) since 2012, we tested the sensitivity of isolates to chloramphenicol and found that 24/211 (11.4%) were fully resistant to this antibiotic.…”
Section: Discussionmentioning
confidence: 89%